TI_GERICHTE 11.2018.120 vom 21. Mai 2019 , Appello contro l'omologazione di una convenzione sugli effetti del divorzio - TI Tribunale d'appello (2019)
Appello contro l'omologazione di una convenzione sugli effetti del divorzio